The Chinese Charcoal Kiln - Chaturvedi, M. D. (Indian Forester)
An underground kiln of the shape of a rectangular ditch measuring 12 ft. × 5 ft. × 6 ft. holding exactly half a chatta∗ of fuel was tried in the Pilibhit Division for the manufacture of charcoal. The ditch was covered with iron sheets rendered air-proof with the help of fine earth. A system of inlet flues and exhausts was devised to control carbonisation. The kiln carbonised wood in about 48 hours, cooled in about 30 hours and yielded charcoal of excellent qualality weighing about 20 per cent. Of the wood used.